Oncolysate-loaded Escherichia coli bacterial ghosts enhance the stimulatory capacity of human dendritic cells - Michalek, Jaroslav; Hezova, Renata; Turánek-Knötigová, Pavlína; Gabkova, Jana; Strioga, Marius; Lubitz, Werner; Kudela, Pavol (Cancer immunology and immunotherapy, 2017)
The natural adjuvant properties of bacterial ghosts (BGs) lie within the presence of intact pathogen-associated molecular patterns on their surface. BGs can improve the direct delivery, natural processing and presentation of target antigens within dendritic cells (DCs). Moreover, sensitization of human DCs by cancer cell lysate (oncolysate)-loaded BGs in the presence of IFN-α and GM-CSF enhanced DC maturation as indicated by an increased expression of maturation markers and co-stimulatory molecules, higher production of IL-12p70 and stimulation of significantly increased proliferation of both autologous CD4(+) and CD8(+) T cells compared to DCs matured in the presence of purified lipopolysaccharide. The induced T cells efficiently recognized oncolysate-derived tumor-associated antigens expressed by cancer cells used for the production of oncolysate. Our optimized one-step simultaneous antigen delivery and DC maturation-inducing method emerges as a promising tool for the development and implementation of next-generation cellular cancer immunotherapies.
Keywords: Phenotype; lipopolysacharidy; Cell Line, Tumor; Escherichia coli; Dendritic Cells; dendritické buňky; Interleukin-12; Immunotherapy, Adoptive; buněčná diferenciace; lidé; imunoterapie adoptivní; CD8-Positive T-Lymphocytes; Lipopolysaccharides; glioblastom; Glioblastoma; CD4-pozitivní T-lymfocyty; CD8-pozitivní T-lymfocyty; interleukin-12; Cell Differentiation; CD4-Positive T-Lymphocytes; fenotyp; nádorové buněčné linie; Humans